2000
DOI: 10.1300/j010v30n01_05
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Values and Experience in Determining Social Workers' Attitudes Toward Euthanasia and Assisted Suicide

Abstract: This article reports results of a study examining the impact of personal and professional values and experience on 122 hospital social workers' attitudes toward euthanasia and assisted suicide. Respect for self-determination was rated as the most important consideration in end-of-life issues. Predictors of social workers' agreement that euthanasia should be legal were: self-determination, religious beliefs, educational level (BSW/MSW), and for assisted suicide were: religious beliefs, belief in the potential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
7

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 21 publications
1
15
0
7
Order By: Relevance
“…Social work researchers have contributed little to our understanding of suicide (Joe & Niedermeier, 2008), despite the fact that many social workers are in positions of possible intervention with suicidal clients (Feldman & Freedenthal, 2006;Jacobson et al, 2004). Although social worker attitudes toward voluntary euthanasia and assisted suicide have been explored (Csikai, 1999a(Csikai, , 1999bErlbaum-Zur, 2005;Ogden & Young, 2003), their attitudes toward suicide remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Social work researchers have contributed little to our understanding of suicide (Joe & Niedermeier, 2008), despite the fact that many social workers are in positions of possible intervention with suicidal clients (Feldman & Freedenthal, 2006;Jacobson et al, 2004). Although social worker attitudes toward voluntary euthanasia and assisted suicide have been explored (Csikai, 1999a(Csikai, , 1999bErlbaum-Zur, 2005;Ogden & Young, 2003), their attitudes toward suicide remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of social research in the field of social work suggest that training in professional ethics affects the attitudes of social workers, the beneficiaries, and decision-making, particularly for those working in hospitals (Csikai, 1999;Boland, 2006). Ethics and training are important steps towards the acquisition of skills necessary to manage ethical dilemmas (Dolgoff, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Although prevailing social values have a direct impact on the development of ethical standards (Boland, 2006, Csikai, 1999, personal and professional values are also regarded as an integral part of ethical decision-making (Abramson, 1996;Dolgoff, 2005;Freud & Krug, 2002;Hopkins, 1997;Mattison, 2000;Pike, 1996). There is a limited research that explores the relationship between moral values and decision-making in the field of social work, I In spite of the importance of this subject.…”
Section: ) General Practice Requires the Application Of Critical Thmentioning
confidence: 99%
“…The author suggests that specific beliefs and attitudes are associated to the fundamental values which are central and more stable. Csikai (1999) found that personal values play a significant role in predicting attitudes towards euthanasia and assisted suicide among gatekeepers. The questionnaire consists of 18 instrumental values and 18 end-state (terminal) values, which are ranked by the respondent in a hierarchy from 1 (most preferable) to 18 (least desirable).…”
Section: Rvsmentioning
confidence: 99%